Postpartum HELLP syndrome complicated with large subcapsular liver hematoma. Issue 5 (15th September 2022) - Naqvi, Syed; Hassnain, Syed; Yousaf, Amman; Muhammad, Shoaib; Cabrera, Diego
Abstract: Subcapsular hematoma of the liver is a potentially fatal complication of pregnancy-related hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome. In turn, HELLP syndrome is one of the most critical complications of preeclampsia. We present a case of a 31-year-old woman who developed a subcapsular liver hematoma in the postpartum period secondary to HELLP syndrome. The diagnosis was made based on the clinical features, radiological investigation, and laboratory values. She was managed with fluids, intravenous steroids, and rigorous monitoring in the intensive care unit before being moved to a tertiary care center with hepatic surgery and interventional radiology capabilities.